The Stability Analysis of A-Quartic Functional Equation - Chinnaappu Muthamilarasi (MDPI AG, 2021)
In this paper, we study the general solution of the functional equation, which is derived from additive–quartic mappings. In addition, we establish the generalized Hyers–Ulam stability of the additive–quartic functional equation in Banach spaces by using direct and fixed point methods.